2013
DOI: 10.1002/jid.2973
|View full text |Cite
|
Sign up to set email alerts
|

Openness and Growth: Still an Open Question?

Abstract: Abstract:We review recent empirical literature on the relationship between openness and the level of national income or, nearly equivalently, trade liberalisation and economic growth. Recent advances reinforce the presumption of a positive causal link from trade to income, especially by solving endogeneity issues more carefully than heretofore and by allowing for heterogeneity between countries. Heterogeneity suggests that low-income countries may benefit less from trade liberalisation than do other countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…These results mean that internationalisation in trade activities in LMCs and UMCs results in benefits for domestic product spaces through improvements in economic complexity, whereas it seems to be a harmful factor in HICs. The positive impact of trade openness on economic complexity contributes to an extensive literature that trade openness brings benefits for economic development (Winters & Masters, 2013), especially in low‐ and middle‐income countries (Benita, 2019; Raghutla, 2020). In fact, the literature shows that trade openness could induce export diversification (Agosin et al, 2012), which seems to be stronger in low‐ and middle‐income countries as their economies have more space for diversification and economic expansion (Balavac & Pugh, 2016; Makhlouf et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…These results mean that internationalisation in trade activities in LMCs and UMCs results in benefits for domestic product spaces through improvements in economic complexity, whereas it seems to be a harmful factor in HICs. The positive impact of trade openness on economic complexity contributes to an extensive literature that trade openness brings benefits for economic development (Winters & Masters, 2013), especially in low‐ and middle‐income countries (Benita, 2019; Raghutla, 2020). In fact, the literature shows that trade openness could induce export diversification (Agosin et al, 2012), which seems to be stronger in low‐ and middle‐income countries as their economies have more space for diversification and economic expansion (Balavac & Pugh, 2016; Makhlouf et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…A one per cent increase in Mozambique's GDP is not going to influence the incentives for migration -and at one percent of GDP (approximately $14.2 billion for Mozambique in 2012), it would cost $142 million a year. Even if aid were much more effective than Clemens et al's calculations suggest, and even given the much stronger growth effects likely to emanate from increased trade (see, for example, Winters and Masters, 2013), the qualitative story would not be much changed inside several decades.…”
Section: Do Trade and Aid Influence Migration?mentioning
confidence: 96%
“…Were (2015) provided a comparative analysis among African countries using standard growth regression. A compact review of recent empirical studies on trade openness and growth was provided by Winters and Masters (2013). Although the emphasis in the earlier literature was on exports, it was also confirmed that imports supported economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%